2014
DOI: 10.1603/en13194
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofEntomophaga maimaiga(Entomophthorales: Entomophthoraceae) on Outbreak Gypsy Moth Populations (Lepidoptera: Erebidae): The Role of Weather

Abstract: The fungal pathogen Entomophaga maimaiga Humber, Shimazu, and Soper is prevalent in gypsy moth [Lymantria dispar (L.)] populations throughout North America. To understand how weather-related variables influence gypsy moth-E. maimaiga interactions in the field, we measured fungal infection rates at 12 sites in central Pennsylvania over 3 yr, concurrently measuring rainfall, soil moisture, humidity, and temperature. Fungal mortality was assessed using both field-collected larvae and laboratory-reared larvae cage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…This positive relation to density is what we would expect for LdMNPV [55], and has also been found for E. maimaiga in some studies [27,56], but is not always the case (e.g. [35]), probably because environmental conditions also impact E. maimaiga infection [57] and can restrict density-related responses.…”
Section: (B) Associations With Host Densitysupporting
confidence: 85%
See 1 more Smart Citation
“…This positive relation to density is what we would expect for LdMNPV [55], and has also been found for E. maimaiga in some studies [27,56], but is not always the case (e.g. [35]), probably because environmental conditions also impact E. maimaiga infection [57] and can restrict density-related responses.…”
Section: (B) Associations With Host Densitysupporting
confidence: 85%
“…Historically, before the fungus arrived in the USA, the virus caused epizootics ending host outbreaks [57] and the community of introduced parasitoids caused higher mortality than we found [46,47]. The fungal pathogen now outcompetes parasitoids within gypsy moth caterpillars at a range of host densities.…”
Section: Resultsmentioning
confidence: 60%
“…This is the second study to show that weather conditions before gypsy moth egg hatch are associated with subsequent E. maimaiga infection levels (Hajek and Tobin 2011). Other studies have also demonstrated repeatedly that when E. maimaiga is active (the fungus is inactive 10 months of the year), infection prevalence is positively related to moisture levels (Hajek 1999;Reilly et al 2014). In contrast, LdNPV infections were positively associated with precipitation in April and June but not May.…”
Section: Discussionmentioning
confidence: 67%
“…Entomophaga maimaiga and LdNPV can co-infect hosts (Malakar et al 1999) and are frequently both present in higher density L. dispar populations (AEH, unpublished data; Reilly et al 2014). …”
Section: Study Systemmentioning
confidence: 99%
“…Unlike bark beetle attacks, which typically kill trees quickly, severe defoliation over multiple years is usually required to kill trees, particularly in deciduous species (Van Asch & Visser, ). Natural enemies, which generally have a larger limiting effect on defoliator population dynamics than on bark beetles, are affected by temperature (especially predators and parasites) and precipitation (especially entomopathogens) (Jamieson et al ., ; Reilly et al ., ).…”
Section: Drought and Insect Mortality Pathwaysmentioning
confidence: 97%